An anti-history about transgender inclusion in the Brazilian labor market - Luna, Camilla Pinto; Barros, Denise Franca (Emerald Publishing Limited, 2023)
Though still a journey filled with resistance, a struggle for space and the recognition of rights, the Brazilian LGTBQIA+ population has achieved some legal and social progress. Yet transphobia in Brazilian society is one of the biggest problems for trans people; this social exclusion generates a multitude of difficulties when entering the formal labor market. Even companies that are considered LGBTQ+ friendly often focus more on "LGB" than "TQ+". An ANTi-History about Transgender Inclusion in the Brazilian Labor Market answers repeated calls to correct the neglect of voices from the global south and the scarcity of work on gender and transgender peoples in organizational history. Luna and Barros investigate socio-political relations of actors-networks, highlighting the main mobilizations and demobilizations in the trajectory of transgender people inclusion in organizations in Brazil. (Re)assembling a version of history about transgender people's labor inclusion and introducing a network rhizome, the authors rescue memories in the transgender-society-labor market relationship, revealing the silences and broader context surrounding recent employability initiatives. Speaking to management academics and reaching beyond to inform actions, policies, and initiatives for the inclusion of trans people in the job market, An ANTi-History about Transgender Inclusion in the Brazilian Labor Market is a novel and extremely important addition to the field of Organizational Studies.
Keywords: Transgender people -- Employment -- Brazil.; Discrimination in employment -- Brazil.; Labor market -- Brazil.; Business & Economics, Workplace Harassment & Discrimination.; Personnel & human resources management.; elektronické knihy; electronic books